Representation of Korean Values Sustainability in American Remake Movies - Muhammad Fithratullah (TEKNOSASTIK, 2021)
Globalization has triggered Korean movies more competitive. Many scholars and critics considered American and Korean popular culture domination. Hollywood has experiences in shaping the lifestyle of the world. This research aims to figure out sustainable values represented on American remakes of Korean popular movies. It also has purpose to find out the reason behind the sustainability. The study applied semiotic theories from Christian Metz. Representation approach was also applied to reveal the values beneath the transnational remakes supported by qualitative methods. The results revealed that there were several Korean values remain in the remake version of Korean American movies. It also revealed that the audience demands and taste mainly influence sustainability of values as well as universality of the values believed by the audience becomes the driving force of the sustainability represented in the remake movies.